A Study on the Relation Between Education and Economic Development: The Impact of Education on Economic Development (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Education, apart from producing human skills needed for the developmentof an economy is instrumental in making people aware of the available economicopportunities and social services that they can benefit from. It also helps inthe satisfaction of other basic needs through creation of awareness onnecessities of personal hygiene, household sanitation, clean water, nutritionalrequirements and primary health care. In sum, development affects botheducation and fulfillment of other basic needs and is affected by them, whileeducation and other basic needs are also interrelated.